Nutrient contributions and biogas potential of co-digestion of feedstocks and dairy manure. (June 2017) - Ma, Guiling; Neibergs, J. Shannon; Harrison, Joseph H.; Whitefield, Elizabeth M.
Highlights: Characterization of nutrient flow in a full scale anaerobic digester. Confirmation of simple chemical measures for estimating biogas potential. Performance of an anaerobic digester managed with co-digestion of pre-consumer food wastes. Abstract: This study focused on collection of data on nutrient flow and biogas yield at a commercial anaerobic digester managed with dairy manure from a 1000 cow dairy and co-digestion of additional feedstocks. Feedstocks included: blood, fish, paper pulp, out of date beverages and grease trap waste. Mass flow of inputs and outputs, nutrient concentration of inputs and outputs, and biogas yield were obtained. It was determined that manure was the primary source of nutrients to the anaerobic digester when co-digested with feedstocks. The percentage of contribution from manure to the total nutrient inputs for total nitrogen, ammonia-nitrogen, phosphorus and total solids was 46.3%, 67.7%, 32.8% and 23.4%, respectively. On average, manure contributed the greatest amount of total nitrogen and ammonia-nitrogen. Grease trap waste contributed the greatest amount of phosphorus and total solids at approximately 50%. Results demonstrated that a reliable estimate of nutrient inflow could be obtained from the product of the nutrient analyses of a single daily composite of influent subsamples times the total daily flow estimated with an in-line flow meter. This approach to estimate total daily nutrient inflow would be more cost effective than testing and summing the contribution of individual feedstocks. Data collected after liquid-solid separation confirmed that the majority (>75%) of nutrients remain with the liquid effluent portion of the manure stream. It was demonstrated that the ash concentration in solids before and after composting could be used to estimate the mass balance of total solids during the compost process. This data confirms that biogas or methane yield could be accurately measured from the ratio of % volatile solids to % total solids.